Teacher Motivation and Professional Identity within the Expanded Career Progression (ECP) System: A Case Study in a Philippine Public School - Dallong, Chona Myrth (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the lived experiences of teachers with the Expanded Career Progression (ECP) System in a semi-rural Philippine public school, particularly in relation to teacher motivation, professional identity, and career progression. Anchored in Self-Determination Theory and Identity Theory, the study employed a simple qualitative research design involving all teachers of San Antonio North Elementary School, including one Alternative Learning System teacher, through total population sampling. Data were gathered using semi-structured interviews, focus group discussions, document review, field notes, and classroom observations where permitted. Thematic analysis was used to examine teachers’ experiences in terms of autonomy, competence, relatedness, commitment, engagement, self-concept, role perception, social validation, challenges, opportunities, and recommendations. Findings revealed that the ECP System strengthened teacher competence through training, mentoring, and peer sharing, and enhanced relatedness through collaboration and community involvement. However, its influence on autonomy remained limited due to centralized decision-making, administrative workload, unclear promotion guidelines, heavy reporting, and limited resources. The system also supported teachers’ evolving professional identity as mentors, teacher-leaders, role models, and contributors to school growth, although recognition remained partly tied to paperwork and clerical tasks rather than classroom innovation. The study concludes that the ECP System has potential to support teacher development, but its implementation should be refined by simplifying requirements, reducing paperwork, clarifying promotion standards, and giving greater value to instructional leadership and classroom excellence. The study supports SDG 4 on Quality Education, SDG 8 on Decent Work and Economic Growth, SDG 11 on Sustainable Cities and Communities, SDG 16 on Strong Institutions, and SDG 17 on Partnerships for the Goals. Its sustainability impact lies in strengthening teacher motivation, institutional responsiveness, community support, and policy improvement in semi-rural education contexts.